Effect of Tryptophan and Glutamic Acid on Morphological Traits of Iranian and Afghan Saffron - Mukhlis, Naseer; Kheiry, Azizollah; Nasrat, Nasrullah (Integrated Journal for Research in Arts and Humanities, 2023)
In order to investigate the effect of amino acids tryptophan and glutamic acid on the morphological traits of saffron medicinal plant, a factorial experiment was conducted in the form of a randomized complete block design in three replications in 2018 in the research farm of Zanjan University. Experimental treatments include three genotypes (Iranian, Afghani 1 and Afghani 2) as the main treatment and amino acid tryptophan at two levels (1 and 2 mM) and glutamic acid at two levels (1 and 2 mM) as secondary treatments. They were considered as witnesses. The results showed that tryptophan and glutamic acid treatments had a significant effect (P ≤ 0.01) on most of the investigated traits including number of flowers, dry weight of flowers, vegetative body. The highest content of number of flowers and dry weight of flowers were observed, respectively, 34.6 and 37.36 mg of dry weight. Also, the performance traits of flower fresh weight, stigma dry weight, showed significant difference (P ≤ 0.05) under the treatment of two amino acids. The maximum yield of phenol and flavonoid in 2 mM tryptophan concentration was 0.35 and 0.026 mg/g/ha, respectively, and the lowest yield in 1 mM glutamic treatment was 0.34 and 0.02 mg/g/ha, respectively. In total, different levels of tryptophan and glutamic acid can have an effective role in improving the morphological traits and production of this product. The use of 1 mM glutamic acid to produce the maximum vegetative body of the plant, the treatment of 1 and 2 mM of both amino acids to improve physiological indicators and 1 mM of glutamic acid for the performance of secondary metabolites is desirable and recommended for the purpose.